QUARANTINE TAHFIZH ALQURAN PROGRAM (STUDY ANALYSIS IN INLIGHT QUR‘ANIC CENTER, BAITUL QUR‘AN, AND TAHFIZH QUR‘AN FOUNDATION AL-FAWWAZ MEDAN) - Syaukani, Neliwati, Muhammad Ruslan (Pascasarjana UIN Sumatera Utara, 2019)
Abstract: This research aims to describe the Tahfizh Qur’an Quarantine Program at the Inlight QuranicCenter, Baitul Quran Medan, and the Tahfidzul Quran Al-Fawwaz Medan Foundation.This type ofresearch is descriptive with a qualitative approach. The sources of information of this research are theTahfizh mudir (leaders), teachers, and tahfizh participants and some figures who know about the tahfizhquarantine program. Data collection techniques carried out through interviews, participant observation,and documents. Data analysis technique is done by data reduction, data presentation, and drawingconclusions / verification. The findings in this study are four, namely: (1) The implementation of theTahfizh Al-Qur’an Quarantine Program implemented by the Foundation of the National Tahfidz AlquranFoundation Inlight Quranic Center, Baitul Quran, and the Tahfidzul Quran Al-Fawwaz Medan Foundationis by (a) carrying out the preparation process, determining Tahfiz quarantine schedule provided generallythree times a year the implementation of the quarantine program, namely: Tahfizh Quarantine holidayprogram mid-semester, Tahfizh Quarantine Quarantine Program and, Tahfizh Quarantine QuarantineProgram at the end of semester program (b) The process of implementing the Tahfizh QuarantineProgram and (c) Output process or Tahfizh Quarantine Graduation Program (2) Supporting factors inthe Quarantine Quarantine Program at b. inlight Quranic center, Baitul Quran, and Tahfidzul QuranFoundation Al-Fawwaz medan, namely: Motivation in memorizing the Qur’an by targeting, strengtheninginterest / motivation, Time in implementing the Tahfizh of the Koran, supporting facilities and inscriptionsin the quarantine program and financing the quarantine Quarantine program (3 ) Obstacles in theQafiz Quarantine Quarantine Program at the Inlight Quranic Center, Baitul Quran, and the TahfidzulQuran Al-Fawwaz Foundation, Medan, namely that the participants of Tahfizh still need to enter theQur’an recitation program, the Tahfizh Quarantine Place which is not yet standard, the relatively expensiveaccommodation funding. (4) Efforts to overcome the inhibiting factors of the tahfizh quarantine programare by (a) conducting a tahfizh teacher regeneration program, (b) Organizing a Training for trainers foreducators in the tahfizh program (c) Motivating the participants of the quarantine.Keywords: Quarantine, Tahfizh, Qur’an